Sobre o teorema da aplicação inversa e o teorema da função implícita. - CASTRO, Adriano da Silva (2024)
In this work, we will study two of the most important theorems of Analysis in Rn, more precisely, the Inverse Application Theorem and the Implicit Function Theorem. Before we formally present the theorems, we will make an introduction with historical development and we will also study definitions, theorems and lemmas that will help us to understand and demonstrate the two desired theorems. After that, we will see some applications of these theorems in order to highlight their importance.